Specific interaction between genotype, smoking and autoimmunity to citrullinated alpha-enolase in the etiology of rheumatoid arthritis. - Mahdi, H; Fisher, B; Källberg, H; Plant, D; Malmström, V; Rönnelid, J; Charles, P; Ding, B; Alfredsson, L; Padyukov, L; Symmons, D; Venables, P; et al. (2009)
Gene-environment associations are important in rheumatoid arthritis (RA) susceptibility, with an association existing between smoking, HLA- DRB1 'shared epitope' alleles, PTPN22 and antibodies to cyclic citrullinated peptides (CCP). Here, we test the hypothesis that a subset of the anti-CCP response, with specific autoimmunity to citrullinated alpha-enolase, accounts for an important portion of these associations. In 1,497 individuals from three RA cohorts, antibodies to the immunodominant citrullinated alpha-enolase CEP-1 epitope were detected in 43-63% of the anti-CCP-positive individuals, and this subset was preferentially linked to HLA-DRB1*04. In a case-control analysis of 1,000 affected individuals and 872 controls, the combined effect of shared epitope, PTPN22 and smoking showed the strongest association with the anti-CEP-1-positive subset (odds ratio (OR) of 37, compared to an OR of 2 for the corresponding anti-CEP-1-negative, anti-CCP-positive subset). We conclude that citrullinated alpha-enolase is a specific citrullinated autoantigen that links smoking to genetic risk factors in the development of RA.